2009
DOI: 10.1897/ieam_2008-058.1
|View full text |Cite
|
Sign up to set email alerts
|

A long‐term, multitrophic level study to assess pulp and paper mill effluent effects on aquatic communities in four us receiving waters: Lessons learned

Abstract: Lessons learned from the development, implementation, and initial 8 y of study findings from a long-term study to assess the effects of pulp and paper mill effluents on receiving waters are summarized as a conclusion to a series of articles (this issue) on study findings. The study, based on industry-defined information needs, was developed via a science-based experimental design into a long-term (>10 y) watershed-scale monitoring program that integrated in-stream population/ community assessment, laboratory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The results of laboratory fathead minnow (Pimephales promelas) full life-cycle studies with the 4 effluents are described by Borton et al (2009) and represent an additional approach to assessing fish reproduction effects beyond those measured directly through long-term, in-stream community assessment. Finally, a compilation and overview of the lessons learned from the initial years of the LTRWS are presented by Hall, Fisher, et al (2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of laboratory fathead minnow (Pimephales promelas) full life-cycle studies with the 4 effluents are described by Borton et al (2009) and represent an additional approach to assessing fish reproduction effects beyond those measured directly through long-term, in-stream community assessment. Finally, a compilation and overview of the lessons learned from the initial years of the LTRWS are presented by Hall, Fisher, et al (2009).…”
Section: Resultsmentioning
confidence: 99%
“…The 13-y path to develop, implement, and carry out especially the initial years of the study provided an opportunity to reflect on what worked well, and not so well, in the LTRWS. These lessons learned are recounted in the last article of this series (Hall, Fisher, et al 2009), along with an overview of findings related to pulp and paper mill effluent effects from the initial years of the study.…”
Section: Resultsmentioning
confidence: 99%
“…There is, however, room within the monitoring program to seek more definitive information that can withstand deeper scrutiny, provide compelling evidence, and ultimately lead to better management decisions. Modifying monitoring with the intent of optimizing the utility of the information provided by the program could be easily described as managing adaptively, including the lessons learned and actions taken during an initial optimization period (Hall et al ). These latter aspects are more closely aligned with the initial steps or an early phase in the adaptive monitoring scheme described here, rather than the modeling normally included in classic adaptive management.…”
Section: Ideal Initial Steps For Implementing An Adaptive Monitoring mentioning
confidence: 99%
“…A series of papers was published in 2009 reporting on fi ndings from the fi rst eight years of the LTRWS (Borton et al 2009;Flinders et al 2009aFlinders et al , 2009bFlinders et al , 2009cHall et al 2009aHall et al , 2009bHall et al , 2009cLandis and Thomas 2009). Conclusions reached during this initial period of the study provide a "weight of evidence" founded on both instream and laboratory-based assessment for an absence of effl uent effects for the four mill discharges studied (Table 2).…”
Section: Long-term Receiving Water Studiesmentioning
confidence: 99%
“…(Envirozine 2004). Conversely, Hall et al (2009c) reported that "following 8 y of monitoring the weight of evidence suggests an absence of instream population/ community effects downstream of the mill discharges" on four U.S. receiving waters. The differences in conclusions may not be refl ective of whether research for these two respective programs was good or bad, but rather that different approaches were taken to identify whether and the extent to which effl uent effects were present.…”
Section: Introductionmentioning
confidence: 99%